2006
DOI: 10.1177/0956247806069608
|View full text |Cite
|
Sign up to set email alerts
|

The peri-urban water poor: citizens or consumers?

Abstract: Using the results of a comparative three-year research project in five metropolitan areas, this article reviews a range of practices in accessing water and sanitation by peri-urban poor residents and producers. It starts from the observation that neither centralized supply policies nor the market through, for example, large-scale profit-making enterprises are able to meet their needs. Although they are consumers insofar as they have no option but to pay market prices for water (and often for sanitation), the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 10 publications
1
113
0
5
Order By: Relevance
“…The conventional urban-rural divide has since long given way to include also a third type of landscape: the peri-urban area, a transitional zone between the city and its hinterland (Rauws and de Roo 2011). However, as shown by Allen et al (2006), peri-urban dwellers-in particular the poor-are often left to their own devices when it comes to realizing their human rights to water and sanitation because their needs, practices and private solutions remain "invisible" to the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional urban-rural divide has since long given way to include also a third type of landscape: the peri-urban area, a transitional zone between the city and its hinterland (Rauws and de Roo 2011). However, as shown by Allen et al (2006), peri-urban dwellers-in particular the poor-are often left to their own devices when it comes to realizing their human rights to water and sanitation because their needs, practices and private solutions remain "invisible" to the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, sanitation, access to clean water, and its sustainability are India’s one of the most urgent concerns. The comparative case study of five cities by Allen et al [26] showed that the inadequacy of public policies and private initiatives to combat the lack of clean water results in higher water prices for the peri-urban poor, which encourages them to use alternate means to access water. Anand’s study [27] in the slums of Mumbai expanded this notion, stating that slum dwellers’ access to water depends on complex cultural, political and empirical factors.…”
Section: Resultsmentioning
confidence: 99%
“…the recognition of non-conventional practices and their articulation to the formal system under new governance regimes (Allen et al, 2006). In the absence of appropriate support, many informal strategies, such as the use of wastewater for irrigation, also carry with them significant avoidable risks to health and wellbeing alongside the obvious benefits (Bradford et al, 2003, page 157;Singh et al, 2010).…”
Section: Policy Research In Relation To Peri-urban Water Management Imentioning
confidence: 99%
“…As such, peri-urban areas occupy "unique space, in that they are simultaneously sustained and imperiled by the dynamics of the urban economy" (Friedberg, 2001, page 353). As a concept, peri-urban can be seen as instances where rural and urban features co-exist, in environmental, socio-economic and institutional terms (Allen et al, 2006). In whatever way the peri-urban is defined, questions about the implications of current development trajectories for the health and livelihoods of affected communities are pertinent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation